Xenarthran synsacrum morphology and evolution - Galliari, Fernando Carlos (2019)
Xenarthra is unique in having striking features in the axial skeleton, usually very different from the rest of the eutherian clades. Some of these features are widely spread among the members of the group (e.g., the presence of xenarthrales in most cingulates and all pilosans, and the synsacrum with sacroischial union to the pelvis in almost all xenarthrans) and others are restricted to some taxa (e.g., deviated number of cervical vertebrae in Bradypus and Choloepus). In this study, we aim to explore the great diversity of vertebral elements composing the xenarthran synsacrum within a phylogenetic framework. Vertebral counts of the adult synsacrum was obtained from almost all extant genera, with the exception of Calyptophractus, and several fossils. The modal number of vertebrae from the adult synsacrum was mapped onto a composite phylogeny of Xenarthra. The ancestral number of synsacrals for Xenarthra was recovered as ambiguous, although one of the optimizations recorded a number of six synsacrals, probably three iliac and three post-iliac vertebrae. The clade Cingulata is characterized by a high number of vertebrae forming the synsacrum (eight synsacrals), which is fused to the ischium through the tip of the transverse processes of the most posterior vertebrae. In pilosans, the ancestral number of synsacral vertebrae seems to be lower, probably formed by five or six vertebrae, and the union with the ischium is achieved through the base of the transverse processes of the most posterior vertebrae. Two exceptions stand out, one involving the extant suspensory sloths and Megalocnus, and the other involving a family of ground sloths, the Mylodontidae. A probable relationship of the synsacral number in the different taxa to the lifestyles is discussed.